THE INFLUENCE OF WORK ENVIRONMENT, WORK EXPERIENCE AND JOB TRAINING ON EMPLOYEE PERFORMANCE IN THE MEDAN CITY FIRE SERVICE - Glorya Ginting; Jedidah Perbina Rosa Br Tarigan; Dini Moniza; , Neta Nia Br Sembiring; Jurisman Simanjorang; Sunday Ade Sitorus; SUNDAY ADE SITORUS (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to look at the influence of the work environment, work experience and work training in the Medan City Fire Service and to achieve targets within a company and increase knowledge, skills and carry out training programs to obtain the maximum targets that employees want to achieve. It is known that there is a training problem such as a lack of implementation of training within the company or the educational background of the employee and work discipline. In this study, the population was 152 employees with 62 samples using a simple random sampling technique selected to be respondents. The research method used was quantitative with questionnaire and interview techniques. The R Square value of the coefficient of determination is 12.8% and the value tcount (2.711) > ttable (1.67155) and significance (0.009) < 0.05 for the work environment variable tcount (-1.005) < ttable (1.67155) and significance ( 0.0319) for the work experience variable and tcount (-0.380) < ttable (1.67155) and significance (0.705) for the work training variable so that the Fcount value (2.839) Ftable < (3.09), obtains a significant probability of 0.045<0 .05 So Ho is accepted and Ha is rejected, therefore environmental variables, experience and work training have a simultaneous and significant influence on employee performance at the Medan City Fire Department